Influencing factors of occupational stress and health effect among grassroots medical and health personnel in Xiong’an New Area, Hebei Province based on Bayesian network - Huixia LI; Junqin ZHAO; Lixin YANG; Qiuying DONG; Jinmei SHI; Jianguo LI; Chunxiang ZHAO; Yan GAO (环境与职业医学)
BackgroundGrassroots medical and health personnel are an important component of China's public health system, and guaranteeing their physical and mental health will have a profound impact on the development of China's health service. ObjectiveTo identify potential influencing factors of occupational stress, anxiety, depression, and insomnia as well as their interactions. MethodsIn August 2021, a cross-sectional survey was conducted among all the staff (2675 medical and health personnel) at 7 secondary public hospitals and 8 health institutions in Xiong’an New Area of Hebei Province by cluster sampling. Occupational stress, anxiety, depression, and insomnia were evaluated by the Effort-Reward Imbalance Questionnaire (ERI), the Generalized Anxiety Disorder-7 (GAD-7), the Patient Health Questionnaire-9 (PHQ-9), and the Athens Insomnia Scale (AIS). The bnlearn and gmodels packages of R4.2.1 software were used to construct Bayesian networks on work and personal factors-occupational stress- health effects. The Bayesian network model was visualized by Netica32.0. ResultsAmong the 3018 questionnaires distributed, a total of 2675 valid questionnaires were recovered, with an effective recovery rate of 88.63%. The positive rates of occupational stress, anxiety, depression, and insomnia were 51.48%, 62.13%, 62.50%, and 56.37%, respectively in the grassroots medical and health personnel. The positive rate of occupational stress among the medical and health workers varied by age, educational level, and organization type (P<0.05); the positive rate of anxiety varied by age, marital status, and daily working hours (P<0.05); and the positive rates of depression and insomnia varied by gender, educational level, and overcommitment (P<0.05). The final Bayesian network contained 14 nodes and 18 directed edges, and its prediction accuracy was 85.4%. .Job title, daily working hours, overcommitment and exercise directly associated with occupational stress, and other work and personal factors associated with occupational stress indirectly. Occupational stress associated with insomnia directly or indirectly via anxiety. Anxiety and insomnia associated with reporting depression. ConclusionGrassroots medical and health personnel of Xiong'an New Area, Hebei Province report high levels of occupational stress, anxiety, depression, and insomnia. Occupational stress directly or indirectly associates with anxiety, depression, and insomnia. Work and personal factors associate with occupational stress, and associate with anxiety, depression, and insomnia via occupational stress. Occupational stress may be an early warning factor of general work and personal factors affecting anxiety, depression, insomnia, and other mental health problems. Attention should be paid to the assessment and intervention of occupational stress in medical and health personnel to prevent mental health problems.